Emerging Contaminants in Environmental Pollution: Innovative Approaches to Monitoring and Mitigation Strategies - Khudayr, Ayman Biasm Muhamad; Sultani, Hussein Khudhair Hussein Abd; Mohammed, Zainab Abd Alhussien Mahdi; Kaream, Nour Nizar Abd -Alirdha (American Journal of Biology and Natural Sciences, 2025)
Emerging contaminants (ECs) present a growing environmental challenge due to their persistence, bioaccumulation, and toxic effects, yet there is still a significant knowledge gap regarding their sources, transport mechanisms, and long-term impacts on ecosystems and human health. This article reviews the origins, types, pathways, and effects of emerging pollutants, focusing on pharmaceuticals, personal care products, microplastics, pesticides, and industrial chemicals. Using a comprehensive literature review and case studies, the paper evaluates current monitoring techniques, such as advanced chemical analysis, biological indicators, and remote sensing, alongside innovative mitigation strategies including bioremediation, advanced oxidation processes, and green infrastructure. Findings reveal that although detection methods have improved significantly, existing regulations and removal technologies remain insufficient to fully manage EC risks. Results emphasize the urgent need for integrated and sustainable monitoring frameworks and mitigation strategies. The study contributes to strengthening scientific understanding and policy development for the protection of environmental and human health from emerging contaminants.